Mycobacterium tuberculosis Rv1987 protein attenuates inflammatory response and consequently alters microbiota in mouse lung - Liu, Yingying; Zhang, Jiaqi; Leng, Guangxian; Hu, Junxing; Wang, Wenzhen; Deng, Guoying; Ma, Yufang; Sha, Shanshan (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Healthy lung microbiota plays an important role in preventing Mycobacterium tuberculosis (Mtb) infections by activating immune cells and stimulating production of T-helper cell type 1 cytokines. The dynamic stability of lung microbiota relies mostly on lung homeostasis. In our previous studies, we found that Mtb virulence factor, Rv1987 protein, can mediate host immune response and enhance mycobacterial survival in host lung. However, the alteration of lung microbiota and the contribution of lung microbiota dysbiosis to mycobacterial evasion in this process are not clear so far. Methods M. smegmatis which does not contain the ortholog of Rv1987 protein was selected as a model strain to study the effects of Rv1987 on host lung microbiota. The lung microbiota, immune state and metabolites of mice infected by M. smegmatis overexpressing Rv1987 protein (MS1987) were detected and analyzed. Results The results showed that Rv1987 inhibited inflammatory response in mouse lung and anaerobic bacteria and Proteobacteria, Bacteroidota, Actinobacteriota and Acidobacteriota bacteria were enriched in the lung tissues correspondingly. The immune alterations and microbiota dysbiosis affected host metabolic profiles, and some of significantly altered bacteria in MS1987-infected mouse lung, such as Delftia acidovorans, Ralstonia pickettii and Escherichia coli, led to anti-inflammatory responses in mouse lung. The secretory metabolites of these altered bacteria also influenced mycobacterial growth and biofilm formation directly. Conclusion All these results suggested that Rv1987 can attenuate inflammatory response and alter microbiota in the lung, which in turn facilitates mycobacterial survival in the host.